SMEs and Access to Bank Credit: Evidence on the Regional Propagation of the Financial Crisis in the UK - Hans Degryse; Kent Matthews; Tianshu Zhao (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the sensitivity of banks' credit supply to small and medium size enterprises (SMEs) in the UK to banks' financial condition before and during the financial crisis. Employing unique data on the geographical location of all bank branches in the UK, we connect firms' access to bank credit to the financial condition (i.e., bank health and the use of core deposits) of all bank branches in the vicinity of the firm over the period 2004-2011. Before the crisis, banks' local financial conditions did not influence credit availability irrespective of the functional distance (i.e., the distance between bank branch and bank headquarters). However, during the crisis, we find that SMEs with in their vicinity banks that have stronger financial condition face greater credit availability when the functional distance is low. Our results point to a “flight to headquarters” effect during the financial crisis.
Keywords: G21; G29; L14; 330; financial crisis; credit supply; flight to headquarters; flight to quality; bank organization